Analysis Of The Home Ownership Loan Procedure At Pt. Putri Grage Property - Dewi, Siti Ratna Sari; Maisyah, Nur (Journal of Economics and Business (JECOMBI), 2024)
This study aims to analyze the procedure for granting Home Ownership Loans (KPR) at PT. Putri Grage Property. The procedure was identified through a case study using qualitative methods, with data obtained from interviews, documentation, and direct observation. PT. Putri Grage Property is a property company that independently manages the credit process without involving banks, providing greater flexibility for customers. The main procedures include document submission, data investigation, interviews, field observations, and credit realization.The results of the study indicate that while this procedure facilitates  customers, the absence of bank checks poses challenges in assessing the eligibility of prospective clients. Common issues include low customer interest, incomplete documents, and payment arrears. To address these issues, PT. Putri Grage Property prioritizes trust in customers, offers payment leniency of up to six months, and enhances marketing strategies.